HUBUNGAN ANTARA BUDAYA ORGANISASI DENGAN KEPUASAN KERJA PADA ASN GEN Z DI INDONESIA - Rosyada Salma Ilafisani, Sayyidah Tsabita; Anas Tasya, Rasila Firli; Salma Andinie, Hifi Angellia (Psikologi UHAMKA, 2023)
The State Civil Apparatus (ASN) is the prime mover in realizing national development, whose performance is important to note. The performance of ASNs can not be separated from the influence of job satisfaction, where this is influenced by various factors including workload, salary, promotions, supervision, colleagues, and working conditions. The composition of ASN in Indonesia consists of several generations, namely the younger generation (Gen Z) and the older generation (Gen X and Y). In contrast to Gen X and Y, Gen Z currently tends to pay more attention to job satisfaction factors. According to Gen Z, the performance they put into work must be directly proportional to the results of the job satisfaction they will get. Therefore it is important to measure job satisfaction in ASN Gen Z. The purpose of this study was to determine the level of significance between job satisfaction of ASN Gen Z and organizational culture in the existing bureaucratic system. This study uses a quantitative approach and survey research using the short form Minnesota Satisfaction Questionnaire with 20 statement indicators about various aspects of work. Measurement of work level using a Likert scale and satisfaction scores, and analyzed through a plot correlation test. Respondent data was obtained by distributing questionnaires online to ASN Gen Z. The results showed that there was a significant and positive relationship between the job satisfaction level of ASN Gen Z and organizational culture. In other words, the condition of organizational culture is positively related to the level of job satisfaction. In addition, the results of the study indicate that there are differences in the level of job satisfaction with the culture of government organizations so that it reads that currently not all government organizations uphold a good organizational culture in accordance with the rules. With these results it is hoped that a good organizational culture in the bureaucratic system can be implemented thoroughly and high job satisfaction can be achieved by all ASN.